2013
DOI: 10.1105/tpc.112.107292
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis BPM Proteins Function as Substrate Adaptors to a CULLIN3-Based E3 Ligase to Affect Fatty Acid Metabolism in Plants

Abstract: Regulation of transcriptional processes is a critical mechanism that enables efficient coordination of the synthesis of required proteins in response to environmental and cellular changes. Transcription factors require accurate activity regulation because they play a critical role as key mediators assuring specific expression of target genes. In this work, we show that CULLIN3-based E3 ligases have the potential to interact with a broad range of ETHYLENE RESPONSE FACTOR (ERF)/APETALA2 (AP2) transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 36 publications
4
115
0
Order By: Relevance
“…A second report by the same group demonstrated that 14-3-3 phosphopeptide binding proteins bind to and stabilize WRI1, leading to increased TAG accumulation (Ma et al, 2016). The 14-3-3 binding site was mapped to WRI1 residues 78 to 92, the same region that interacts with the BPM proteins that act as substrate adaptors to a CULLIN3-based E3 ligase (Chen et al, 2013) (Figure 12), leading the authors to hypothesize that 14-3-3 proteins compete with E3-adapter binding, thereby stabilizing WRI1 (Ma et al, 2016). This 14-3-3/BPM1 binding region is immediately adjacent to the KIN10 phosphorylation site (residues 65274) in the first AP2 domain of WRI1 (Figure 12), suggesting potential overlap between the two described phenomena, possibly involving the ubiquitin-proteasomal degradation pathway.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A second report by the same group demonstrated that 14-3-3 phosphopeptide binding proteins bind to and stabilize WRI1, leading to increased TAG accumulation (Ma et al, 2016). The 14-3-3 binding site was mapped to WRI1 residues 78 to 92, the same region that interacts with the BPM proteins that act as substrate adaptors to a CULLIN3-based E3 ligase (Chen et al, 2013) (Figure 12), leading the authors to hypothesize that 14-3-3 proteins compete with E3-adapter binding, thereby stabilizing WRI1 (Ma et al, 2016). This 14-3-3/BPM1 binding region is immediately adjacent to the KIN10 phosphorylation site (residues 65274) in the first AP2 domain of WRI1 (Figure 12), suggesting potential overlap between the two described phenomena, possibly involving the ubiquitin-proteasomal degradation pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Further work will be required to test details of this model. Several previous reports have described proteasomal degradation of WRI1 (Chen et al, 2013;Ma et al, 2015Ma et al, , 2016. One involves a PEST sequence representing a potential phosphorylation site identified in the C-terminal intrinsically disordered region of WRI1 (IDR3-PEST; Figure 11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7) are likely promoted by MYB89 or regulated by unknown TFs, and other unknown TFs might independently act or interact with MYB89 and/or master regulators described here to regulate those genes that were targeted by MYB89. A previous study showed that the loss of BTB/POZ-MATH (BPM) proteins widely affects plant development and causes altered FA contents in Arabidopsis mutant seeds, and BPM proteins function as negative regulators of WRI1 activities by mediating assembly with the CULLIN3-based REALLY INTERESTING NEW GENE E3 ligases core and ultimately causing its degradation via the 26S proteasome (Chen et al, 2013). However, the expression of the BPM genes is not changed in myb89-1 developing seeds compared with wild-type seeds (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During the ubiquitination process, the BTB/POZ protein is required for CULLIN recruitment and also functions as an adaptor to allow binding to the substrate. Recently, roles of BTB/POZ proteins in plant responses to light, ethylene, abscisic acid, and fatty acid biosynthesis have been reported (Weber and Hellmann, 2009;Christians et al, 2012;Chen et al, 2013). LIGHT-RESPONSE BTB1 (LRB1) and BTB2 (LRB2) strongly influence Arabidopsis photomorphogenesis; the lrb1 lrb2 double mutant is hypersensitive to red light and altered in multiple developmental processes, including seed germination, cotyledon opening and expansion, chlorophyll accumulation, shade avoidance, and flowering time (Christians et al, 2012).…”
Section: Introductionmentioning
confidence: 99%